Meningkatkan Kemampuan Analisis Materi PAK Menggunakan Metode PBL bagi Mahasiswa PPG dalam Jabatan Batch-1 2024 - Dicky Aprianto; Yosef Reza Aji Saputra; Aden Syah Wijaya (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This study aims to evaluate the impact of the Problem-Based Learning (PBL) method on students' analytical and critical thinking skills. Data were collected from 230 respondents, consisting of students who participated in learning using the PBL method. The results of the study indicate that PBL has a very positive impact on improving students' critical and analytical thinking abilities. More than 90% of respondents agreed that PBL helped them think deeply and analytically. Group discussions in PBL were also found to be effective in enhancing material comprehension, with most respondents feeling the benefits. PBL also made it easier for students to remember and apply the material by linking theory to practice. Moreover, this method increased students' confidence in analyzing material and helped them draw conclusions based on valid data and arguments. The study concludes that PBL significantly improves students' analytical skills, critical thinking, and material understanding.